2022
DOI: 10.1021/jacs.2c07349
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Transient Luminescent Assemblies Regulated by Trace Water in Organic Solvents

Abstract: Trace water in organic solvents can play a crucial role in the construction of supramolecular assemblies, which has not gained enough attention until very recent years. Herein, we demonstrate that residual water in organic solvents plays a decisive role in the regulation of the evolution of assembled structures and their functionality. By adding Mg(ClO 4 ) 2 into a multi-component organic solution containing terpyridine-based ligand 3Tpy and monodentate imidazole-based ligand M2, the system underwent an unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The excited-state fluorescent molecules are more inclined to interact with polar solvents, which results in a redistribution of the electron density of the solvent. Consequently, this will lead to a decrease in the energy level of the fluorophores in the excited state. , Hence, an alteration in the polarity of the solvent will affect the fluorescence intensity of the fluorophores as well. Significant variations in the fluorescence intensities are observed when the same volume of different polarity solvents, including water, acetone, DCM, and octane, is added to Cs 3 Sb 2 Br 9 PNCs (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The excited-state fluorescent molecules are more inclined to interact with polar solvents, which results in a redistribution of the electron density of the solvent. Consequently, this will lead to a decrease in the energy level of the fluorophores in the excited state. , Hence, an alteration in the polarity of the solvent will affect the fluorescence intensity of the fluorophores as well. Significant variations in the fluorescence intensities are observed when the same volume of different polarity solvents, including water, acetone, DCM, and octane, is added to Cs 3 Sb 2 Br 9 PNCs (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…In a CHCl 3 /THF solution, Zhang et al reported a temporary assembly mechanism where the development of structure and luminescence of assemblies is controlled by small amounts of water. [ 39 ] By manipulating the moisture content and implementing alternative assembly configurations, the system can exhibit various evolutionary pathways, control the lifespan of supramolecular polymers, and modify the temporal luminescent properties of the system.…”
Section: Modulation Of Chirality In Supramolecular Self‐assembly Proc...mentioning
confidence: 99%
“…The nature of the solvent might significantly affect the CPL and CD performance of chiral self-assembled systems in solution due to complex interactions between solvents and solutes, which makes the role of the solvent as the part of supramolecular entities more prominent . In particular, molecular water plays an important role in the construction and stabilization of natural or man-made assemblies and their functionality. , Chirality transitions at low temperatures were observed upon the incorporation of monomeric water molecules into supramolecular polymers of biphenyl tetracarboxamide .…”
Section: Introductionmentioning
confidence: 99%